Association between ultra-processed foods and risk of cancer: a systematic review and meta-analysis - Lian, Ying; Wang, Gang-Pu; Chen, Guo-Qiang; Chen, Hua-Nan; Zhang, Guang-Yong (Frontiers in Nutrition, 2023)
Background: Despite increasing evidence has shown the association of Ultra-processed Foods (UPFs) with cancer risk, the results remain inconclusive. We therefore conducted the meta-analysis to clarify the association by including recently published studies. Methods: A comprehensive search was conducted in PubMed, Embase, and Web of Science to identify all relevant studies from inception to Jan. 2023. To pool data, fixed- or random-effects models were used where appropriate. Subgroup analyses, sensitivity analyses, and publication bias tests were performed. Results: 13 studies (4 cohort and 9 case-control studies) were included in the analysis, with a total of 625,738 participants. The highest UPFs consumption was associated with increased risk of colorectal cancer (OR=1.23, 95% CI: 1.10-1.38), colon cancer (OR=1.25, 95% CI: 1.14-1.36), and breast cancer (OR = 1.10, 95% CI: 1.00-1.20), but not rectal cancer (OR=1.18, 95% CI: 0.97-1.43), prostate cancer (OR = 1.03, 95% CI: 0.93-1.12). In addition, subgroup analyses shown that a positive association between UPFs consumption and colorectal cancer was observed among men (OR = 1.31, 95% CI: 1.15-1.50), whereas no significant association was observed among women (OR = 1.10, 95% CI: 0.94-1.29). Conclusions: The present meta-analysis suggests that high UPFs consumption is associated with a significantly increased risk of certain site-specific cancers especially the digestive tract and some hormone-related cancers. However, further rigorously designed prospective and experimental studies are needed to better understand causal pathways.